KERAGAMAN JENIS SEMUT PENGGANGGU DI PERMUKIMAN BOGOR - Apriyanto .; Upik Kesumawati Hadi; Susi Soviana (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Ants are insects whit a nuisance in residential areas. Overall the presence of ants is strongly influenced by the availability of food, temperature, and humidity. This study aims to determine the diversity, dominance, and abundance of ants species urban settlement of Bogor. The study was conducted on February to June 2015 by purposive random sampling method at 10 markets, 25 restaurants, inside of the 30 houses and at perimeter of 30 house. Ants were collected by bait traps at 180 spots ( markets, restaurants, and inside the houses) and by hand collection at 30 spots of houses perimeter. The results showed that there were 11 ant species of three subfamilies (Dolichoderinae, Formicinae, Myrmicinae) in the markets, restaurants, and inside the houses. While, there were 20 ant species of 6 subfamilies (Dolichoderinae, Formicinae, Myrmicinae, Ponerinae, Proceratiinae, Pseudomyrmecinae) in house perimeters. The highest relative abundance and dominance of ant species in the market and inside the houses was Paratrechina longicornis, while in the restaurants was Anoplolepis gracilipes, Dolichoderus thoracicus was the highest abundance in perimeter of the house. Diversity index of ant species in the four locations were moderate category (H'= 1,2 at the market, H'= 1,6 at the restaurants, H'= 1.5 in the houses, and H'= 2.2 at houses perimeter).